2019
DOI: 10.1152/jn.00655.2018
|View full text |Cite|
|
Sign up to set email alerts
|

Uncertainty in contextual and kinematic cues jointly modulates motor resonance in primary motor cortex

Abstract: Contextual information accompanying others’ actions modulates “motor resonance”, i.e., neural activity within motor areas that is elicited by movement observation. One possibility is that we weigh and combine such information in a Bayesian manner according to their relative uncertainty. Therefore, contextual information becomes particularly useful when others’ actions are difficult to discriminate. It is unclear, however, whether this uncertainty modulates the neural activity in primary motor cortex (M1) durin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 75 publications
2
21
0
Order By: Relevance
“…No modulation of CSE resulted from AO in incongruent contexts. In a second study by Cretu et al (2019), participants observed either full or occluded videos of an actor grasping and lifting a jar using a precision or a whole-hand grip. Color cues preceded observation trials and were manipulated in terms of their informativeness in predicting the upcoming action.…”
Section: Top-down Contextual Modulations During Action Observationmentioning
confidence: 99%
“…No modulation of CSE resulted from AO in incongruent contexts. In a second study by Cretu et al (2019), participants observed either full or occluded videos of an actor grasping and lifting a jar using a precision or a whole-hand grip. Color cues preceded observation trials and were manipulated in terms of their informativeness in predicting the upcoming action.…”
Section: Top-down Contextual Modulations During Action Observationmentioning
confidence: 99%
“…Another recent study comparably found that reliable contextual cues were sufficient to elicit muscle-specific CSE changes when visual kinematic cues were absent, and that CSE modulation was strongest when both contextual and kinematic cues were present 18 . In the authors' framework, M1 is the site of convergence for bottom-up kinematic cues regarding the actual observed action, presumably arriving via the parieto-frontal grasping circuitry which houses mirror neurons 34 , and top-down contextual cues or priors.…”
Section: Task Context Modulates Csementioning
confidence: 88%
“…Stimuli were created by showing a series of three still shots from videos of a hand reaching, grasping and lifting a round jar (9 cm diameter, 14.5 cm height, 1.5 kg weight). These still shots were chosen from videos that were used previously (Cretu, Ruddy, Germann, & Wenderoth, 2019; de Beukelaar, Alaerts, Swinnen, & Wenderoth, 2016). In WHG all fingers were used to grasp the lid of the jar, whereas for the PG, only the thumb and index finger grasped a small knob mounted on the top of the jar.…”
Section: Movement Stimulimentioning
confidence: 99%
“…From the EMG data, peak-to-peak amplitudes of the MEPs were calculated using custom-made Matlab scripts (Matlab 2015, Mathworks, Natick, MA, USA). Data preprocessing was done using the same criteria presented previously (Cretu et al, 2019). Shortly, the root mean square (rms) of background EMG in the period 110 to 10ms before the TMS pulses was calculated and MEPs with background rms higher than 10 μV were excluded.…”
Section: Electromyographic Recordings and Tms Proceduresmentioning
confidence: 99%
See 1 more Smart Citation